Altered gut microbiota profile in patients with generalized anxiety disorder - Jiang, Hai-yin; Zhang, Xue; Yu, Zheng-he; Zhang, Zhe; Deng, Min; Zhao, Jian-hua; Ruan, Bing (Journal of psychiatric research, 2018)
Close relationships have recently been established between gut microbiota and some mental disorders. Here, we performed a systematic comparative analysis of the gut microbiome in patients with generalized anxiety disorder (GAD) and healthy controls (HCs). We first conducted a cross-sectional study of 40 patients with GAD in the active state and 36 HCs. Second, subgroup analysis consisting of 12 antidepressant-naive patients and 22 controls was performed to validate the results. Finally, a prospective study was performed in a subgroup of nine patients with GAD who underwent analysis in the active state of anxiety and in remission. Compared with the HCs, we found markedly decreased microbial richness and diversity, distinct metagenomic composition with reduced short-chain fatty acid (SCFA)-producing bacteria (associated with a healthy status) and overgrowth of bacteria, such as Escherichia-Shigella, Fusobacterium and Ruminococcus gnavus. Unexpectedly, these changes in the genera were not reversed in remissive GAD. This study identified microbiota dysbiosis of gut microbiota in GAD patients, suggesting that targeting the microbiome may be a useful therapeutic and preventive target for GAD.